Contribution of Equilibrium Variables with the High Spike Accuracy of the Position Diagonal Center (4) in the National Volleyball Team Players - Ban Faisal Al-Azzawi (Journal of Global Pharma Technology, 2019)
What is important about this study is whether there is a relationship between the ability to balance and beating overwhelming for the Iraqi national team volleyball? The study aims to identify the percentage of the equilibrium contribution and its variables with the accuracy of the skill of beating the high spike Diagonal center (4) in the players. In the national volleyball team season (2016-2017), the researchers used the descriptive approach in the style of associative relationships to suit the problem of research. The research community included all the players specialized in the high beating of the Iraqi national team applicants in the ball The researchers concluded that the equilibrium variables contributed accurately and quickly to the high landslide of the region (4), and the researchers recommended the emphasis on the stability exercises, which showed a significant contribution and impact in the accuracy And the speed of beating the Diagonal high ground, and the adoption of tests of accuracy and speed in the assessment of the level of the ballots in the national team because it gives greater realism to the level of training.Keywords: High spike, Accuracy and diagonal center.